La Constitución de 1857 y su interludio parlamentario - Pantoja Morán, David (El Colegio de México, A.C., 2008)
For a long time, American scholars have noticed that Mexico experienced  a parlamentary form of government during  the brief period between the end of the Reform War and the landing of the invading troops, which gave place to the Intervention War against imperial claims. despite the significance of this observation, Mexican scholars had virtually ignored it.This work seeks to reveal, through a political, historical, and legal analysis of these events, if such an experience can be described as parlamentary, if the 1857 Constitution shows signs of a parlamentary system, and if this might have been the intention of its authors.